Studies on circularly polarized antennas for small satellites - Luo, Jiayu (2013)
Small satellites, especially nano- and pico-satellites, are attracting increasing attentions from educational institutions, business organizations and amateur groups. Nanyang Technological University is developing Singapore’s first student satellite – VELOX_I. It is a start of VELOX satellites, which is a series of small satellites and will be launched in the next few years. There are some main subsystems in a satellite, and communication system is one of the most important subsystems. Antenna is a key part of communication system. The aim of this thesis is to study and design antennas for small satellites communication. The focus will be design of circularly polarized microstrip patch antenna for the future uses of VELOX series satellites. In this thesis, a novel single-feed circularly polarized microstrip antenna with asymmetric arc-shape boundaries on four edges of a square patch will be presented and investigated. The arc-shape boundaries’ dimensions can be adjusted according to practical needs and achieve a good performance, providing a large flexibility in fabrication and implementation. Also, the proposed design shows good circularly polarized radiation and a large antenna size reduction. Based on this design, a second design is proposed. Compared to previous design, a different substrate is used and a slit is added in the middle of the patch. In this improved design, a high gain is obtained and the circular polarization is realized. Designs with different arc-shape boundaries and slit dimensions are shown and compared. Experimental results are compared with simulated results and a good agreement is shown. The proposed antennas could find a potential application in small satellites such as cube-satellites where space is of primary concern.